OVERVIEW OF MORINGA LEAF PUDDING ADMINISTRATION ON HEIGHT AND WEIGHT IN STUNTED CHILD An. M IN JETIS VILLAGE, KEMANGKON DISTRICT, PURBALINGGA REGENCY VILLAGE - Umaisah, Fitri; Priyatin Sulistyowati; Sudiarto (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Stunting is a condition of failure to thrive in children under 5 years of age due to chronic malnutrition, especially in the first 1.000 days of life (HPK), which is apparent after the child is years old, resulting in the child being shorter than thein peers In Purbalingga Regency, the prevalence of stunting in toddlers is 26,8 %, wasting in toddlers is 6,5 %, and underweight in toddlers 16,1%. The prevalence of stunting in Purbalingga Regency remains relatively high, thus requiring affordable and safe local nutritional interventions to support the growth and development of children under five. One of the alternative approaches to address stunting is through the provision of moringa leaf pudding. This study aimed to determine the changes in body weight and height after the administration of moringa leaf pudding in a stunted toddler over a 14-day intervention. This qualitative case study was conducted on a two-year-old stunted toddler (An. M). The intervention consisted of providing 100 grams of moringa leaf pudding every two days (a total of seven servings) over 14 days. Anthropometric measurements were taken at baseline (before intervention), at the seventh meeting, and at the end of the intervention (fourteenth meeting). In addition, observation of pudding acceptance and a brief interview with the family regarding dietary habits were conducted. After receiving moringa leaf pudding every two days for 14 days, the toddler experienced a weight gain of 0.4 kg and an increase in height of 0.9 cm. Observations indicated that the child accepted the moringa leaf pudding well, although mild boredom occurred midway through the intervention. Interviews with the family revealed that the provision of moringa leaf pudding improved the toddler’s appetite, leading to measurable weight and height gains. The provision of moringa leaf pudding every two days for 14 days had a positive effect on increasing body weight and height in this case of a stunted toddler. Therefore, moringa leaf pudding may serve as an alternative nutritional support to improve the growth of stunted children, particularly in regions with a high prevalence of stunting.